Pratiques archivistiques et écriture de l’histoire en Tunisie, de l’ère de l’imprimé à la révolution numérique - Mabrouk Jebahi (Revue des Mondes Musulmans et de la Méditerranée)
The digital revolution, which began several decades ago, has continued to transform the way we communicate. It has also significantly changed our relationship with documents, sources and memory. Using the example of Tunisia (its recent history and that of its National Archives), this article examines the impact of new information and communication technologies on archival science and historical research. It shows how the work of these two professional communities has been profoundly transformed and their responsibility increased in the face of the many attempts to instrumentalise history.